Expression of Helper and Regulatory T Cells in Atopic Dermatitis: A Meta-Analysis - Zhang, Dao-jun; Hao, Fei; Qian, Tian; Cheng, Hai-xing (Frontiers in Pediatrics, 2022)
Background: Atopic dermatitis (AD) is a common inflammatory skin disease, with the incidence peaks in infancy. A meta-analysis was performed to assess the levels of Th22 cells, Th17 cells, IL-17, and Tregs in peripheral blood of patients with AD. Methods: A comprehensive literature search was performed in PubMed, Embase, China National Knowledge Internet, and Wan-fang Data from inception until July 2021. Two authors independently extracted the data, which were pooled and calculated using Stata15.0 software. Results: A total of 8 studies met the inclusion criteria. Compared with control group, patients with AD had an increased proportion of Th22 cells [WMD=2.07, 95%CI (1.33, 2.81), p<0.001], Th17 cells [WMD=1.04, 95%CI [0.66, 1.43], p<0.001], IL-17 [WMD=17.56, 95%CI (11.10, 24.03), p<0.001] and a decreased proportion of Tregs [WMD=-2.49, 95%CI (-2.93, -2.05), p<0.001] in peripheral blood. The subgroup analysis showed that patients with higher disease severity had higher levels of Th22 [mild: WMD=1.33, 95%CI (1.24, 1.41), p<0.001; moderate: WMD=1.41, 95%CI (1.36, 1.54), p<0.001; severe: WMD=3.46, 95%CI (3.34, 2.81), p<0.001] and lower levels of Tregs [mild: WMD=-1.43, 95%CI (-1.75, -1.11), p<0.001; moderate: WMD=-2.16, 95%CI (-2.46, -1.86), p<0.001; severe: WMD=-2.96, 95%CI (-3.25, -2.67), p<0.001] in peripheral blood compared to healthy controls. Conclusions: The random effect model of the meta-analysis showed patients with AD had an increased proportion of Th22 cells, Th17cells, and IL-17, and a decreased proportion of Tregs in peripheral blood. The results demonstrated that Th22 cells, Th17 cells, IL-17, and Tregs may be involved in the pathogenic mechanisms of AD.